Analysis and Design of Inventory Systems to Improve Management Efficiency at a Small Clinic in Bogor - Wulandari, Stepani Sisca; Pinky Rosalia; Fanky A Sorongan; Niko Silitonga (Edumedia Solution, 2025)
This research aims to analyze the needs and business processes in inventory management at the Irna Dewi Megawati midwife clinic, as well as to design an accounting information system for the inventory of goods using the FIFO (First In First Out) method. Currently, inventory management at the Clinic is carried out manually, relying on notes or receipts from goods distributors, which often leads to errors in inventory data, delays in finding goods data, and difficulties in making reports. This research uses a qualitative method. Data were collected through interviews and observations. The system was developed using the prototyping method, with the initial design created using Balsamiq. The system was created using the PHP programming language, MySQL as the database, and XAMPP as the local database server. The results of this study show that the system can provide accurate inventory data, record incoming and outgoing transactions in real-time, and support clinics in decision-making. With this solution, the inventory management process at the Irna Dewi Megawati midwife clinic becomes more efficient and easier to use by users or staff who do not have an IT background.